2014
DOI: 10.4238/2014.january.14.8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of RFRP gene in pigs and its association with reproductive traits

Abstract: ABSTRACT. RFamide-related peptide (RFRP) gene is a crucial gene of the hypothalamo-pituitary-gonadal axis and plays an important role in reproduction regulation. This study aimed to clone and characterize the pig RFRP gene. We obtained a 645-bp cDNA of pig RFRP gene comprising a 546-bp open reading frame, which encoded a peptide of 188 amino acids. The pig RFRP coding sequences have the identities of 81, 68.8, and 76.1% with their counterparts in humans, mice, and rats, respectively. Real-time polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, in birds, GnIH application decreases testosterone release from gonadotropin-stimulated testes in vitro , pointing to a functional role for gonadal GnIH (58). Later, it was shown that RFRP-3 is synthesized in the gonads of all mammals studied to date (59), including humans (60), non-human primates (61), Syrian hamsters (62), mice (60, 63), rats (64), ewe (65), and pigs (66). Across species, the gonads synthesize RFRP-3 and GPR147 (57, 5961, 63).…”
Section: Rfrp-3 Neurons As Regulators Of the Hypothalamo-pituitary Gomentioning
confidence: 99%
“…Moreover, in birds, GnIH application decreases testosterone release from gonadotropin-stimulated testes in vitro , pointing to a functional role for gonadal GnIH (58). Later, it was shown that RFRP-3 is synthesized in the gonads of all mammals studied to date (59), including humans (60), non-human primates (61), Syrian hamsters (62), mice (60, 63), rats (64), ewe (65), and pigs (66). Across species, the gonads synthesize RFRP-3 and GPR147 (57, 5961, 63).…”
Section: Rfrp-3 Neurons As Regulators Of the Hypothalamo-pituitary Gomentioning
confidence: 99%
“…Consistent with this finding, GnIH/RFRP-3 and GPR147 were spatially and temporally expressed in other vertebrates’ ovaries [ 24 , 29 ]. Moreover, the dynamic expression of RFRP-3 was remarkably different in various species, with slightly high expression in the hypothalamus and pituitary of humans but abundantly expressed in pigs [ 23 , 36 ]. Our study confirmed that GnIH / RFRP-3 and its receptor GPR147 were mainly expressed in yak ovarian cells, and they might regulate the ovarian steroidogenesis function in an autocrine and/or paracrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence has documented a role of RFRP-3 in regulating GnRH and GHRH neuronal expression and function as well as secretion of gonadotrophin and steroid hormones and impacting the expression of Kisspeptin in mammals ( Johnson et al, 2007 ; Ducret et al, 2009 ; Kadokawa et al, 2009 ; Ancel et al, 2012 ; Li et al, 2013 ). The pig RFRP gene was found to be abundantly expressed in the nervous system (cerebellum, cerebrum, hypothalamus, and pituitary) and reproduction system (ovary, oviduct, uterus, and testis), and is thought to be a candidate gene for porcine reproductive traits ( Fang et al, 2014 ).…”
Section: Neuropeptide Modulators Of Gnrh Neuronal Activity Gnrh Secretion and Reproduction That Act Directly On Gnrh Neuronsmentioning
confidence: 99%